Bilateral sacroiliac joint dislocation treated by posterior instrumentation case report and literature review - Fernando Moreno Mateo; Rubén Hernández Ramajo; José María Trigueros Larrea; Silvia Santiago Maniega; Francisco Ardura Aragón; David César Noriega González (Archives of Trauma Research, 2019)
Sacroiliac joint dislocation is an uncommon and potentially life-threatening injury secondary to high-energy trauma. Given that bilateral sacroiliac joint dislocation has rarely been reported, its management constitutes a clinical challenge. The aim of this study was to review the literature available about sacroiliac joint dislocation management and to show an effective and reliable method to treat this kind of injury. Case report. We present a 15-year-old female patient who suffered a complete bilateral sacroiliac joint dislocation. The definitive treatment consisted of bilateral L4-iliac assembly plus right sacroiliac screw assisted by an O-arm navigation system. Surgical instrumentation allowed mobilization and full-weight-bearing a few days after surgery. At the 2-year follow-up, the patient remained asymptomatic. The triangle fixation technique stabilizes the sacroiliac joint and binds the lumbar spine to the pelvis. This method could represent a good option that allows early mobilization and weight-bearing.